2021
DOI: 10.21608/ejhm.2021.196759
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Prognosis, and Outcome in Egyptian Children with Primary Immune Thrombocytopenia: A Single-Center Experience

Abstract: Background: Idiopathic (immune) thrombocytopenic purpura (ITP) is a heterogeneous clinical disorder characterized by immune-mediated platelet destruction. ITP is usually a benign, self-limiting disease in children. Objective: To assess prevalence, prognosis, and outcome of Egyptian children with primary immune thrombocytopenia. Patients and Methods: This cross-sectional study was carried on 80 children (1-13 years) with primary ITP who presented to the Pediatric Hematology Unit and outpatient clinic of Zagazig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Childhood Immune Thrombocytopenia (ITP) is one of the most frequent autoimmune hemorrhagic diseases affecting 5 to 10 children out of every 100,000. Twenty to thirty percent of cases were shown to be prone to chronicity with increased susceptibility to bleeding, infection, and blood malignancy than healthy children ( Beshir et al, 2021 ) ( Li et al, 2020 ). Previous studies demonstrated that when compared to children who received therapeutic regimens, the no therapy group had a significantly higher recurrence and more serious complications ( Makis et al, 2017 ) ( Kühne et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood Immune Thrombocytopenia (ITP) is one of the most frequent autoimmune hemorrhagic diseases affecting 5 to 10 children out of every 100,000. Twenty to thirty percent of cases were shown to be prone to chronicity with increased susceptibility to bleeding, infection, and blood malignancy than healthy children ( Beshir et al, 2021 ) ( Li et al, 2020 ). Previous studies demonstrated that when compared to children who received therapeutic regimens, the no therapy group had a significantly higher recurrence and more serious complications ( Makis et al, 2017 ) ( Kühne et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%